Librarian role in managing scholarly publication: UTM's Library experience - Karno, Md. Razib (2015)
This paper observes the new role of librarians in the university after granting of research university academic status. The paper also looks at the implications of this academic status on research publication and librarian’s new role. The aim of the paper is to establish UTM Staff research trends in their scholarly publication on the basis of academic publications issued for 2013. Data about publications were retrieved from January till December 2013 that indexed and listed from the Scopus and Web of Science databases (WOS). The study has identified one hundred and two subject area listed with 1,730 scholarly publications (not include Student, in press and non UTM Staff collaboration) with 1683.397 Cumulative impact factors. The biggest subject area group is Engineering Electrical & Electronic representing 16% of the total publications. There are two other equally large topic groups, representing 12% of the total publication materials each. They are: Energy & Fuels and Engineering Chemical subject area. This paper also discusses the needs for enhancing the research university requirement includes the following steps: Defining the Impact Factor; identifying top tier journal area trends; conducting searches and collecting the publication and citation data from WOS and Scopus; and analyzing the results.